Modeling stand volume of rubber (Hevea Brasiliensis) plantations in Malaysia using landsat TM / Mohd Nazip Suratman ... [et al.] - Suratman, Mohd Nazip; Bull, Gary; Leckie, Don; LeMay, Valerie; Marshall, Peter (Faculty of Applied Sciences, 2004)
Effective management and appropriate policy for rubber trees (Hevea brasiliensis (Wild, ex Adr. de Juss.) Muell Arg.) require reliable forecasts of resource availability. This study was conducted to develop and validate models for estimating stand volume of rubber plantations in Malaysia. A total of 76 rubber stands were sampled and split into two independent groups: model-building and validation data sets. Regression analyses were used to explore relationships between rubber stand volume and Landsat TM bands and ratio-based indices. Statistically significant models for estimating stand volume were obtained. Coefficients of determination (R ) for the models were all higher than 0.70 and standard error of estimate (SEE) values were lower than 54 m3/ha. Thus, Landsat TM provides an acceptable data source for estimating stand volume of rubber plantations in Malaysia.